An interview study with medical scribes on how their work may alleviate clinician burnout through delegated health IT tasks. (12th February 2021) - Tran, Brian D; Rosenbaum, Kathryn; Zheng, Kai
Abstract: Objectives: To understand how medical scribes' work may contribute to alleviating clinician burnout attributable directly or indirectly to the use of health IT. Materials and Methods: Qualitative analysis of semistructured interviews with 32 participants who had scribing experience in a variety of clinical settings. Results: We identified 7 categories of clinical tasks that clinicians commonly choose to offload to medical scribes, many of which involve delegated use of health IT. These range from notes-taking and computerized data entry to foraging, assembling, and tracking information scattered across multiple clinical information systems. Some common characteristics shared among these tasks include: (1) time-consuming to perform; (2) difficult to remember or keep track of; (3) disruptive to clinical workflow, clinicians' cognitive processes, or patient–provider interactions; (4) perceived to be low-skill "clerical" work; and (5) deemed as adding no value to direct patient care. Discussion: The fact that clinicians opt to "outsource" certain clinical tasks to medical scribes is a strong indication that performing these tasks is not perceived to be the best use of their time. Given that a vast majority of healthcare practices in the US do not have the luxury of affording medical scribes, the burden would inevitably fall onto clinicians' shoulders, which could be a major source for clinician burnout. Conclusions: Medical scribes help to offload a substantial amount of burden from clinicians—particularly with tasks that involve onerous interactions with health IT. Developing a better understanding of medical scribes' work provides useful insights into the sources of clinician burnout and potential solutions to it.